Panelists’ Assessment of Fish Chili Sauce with Different Packaging and Shelf Time on Quality - Ni Made Dermadi; Dewa Gede Semara Edi; I Made Kawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Panelists are a reflection of consumers in assessing the suitability of a product. Organoleptically, panelists can determine quality fish chili sauce. In this research, Fish chili Sauce contains 10% fermented tuna meat, so it has a distinctive taste. In storage for three weeks, the quality of the fish sauce will change. The extent of the changes that have occurred will be assessed by the panelists. The aim of the research is to get quality fish chili sauce in certain packaging with the longest shelf life. Using a nested experimental method with two factors, factor I type of packaging, factor II storage time, repeated three times. The best research results, Fish chili Sauce with Glass Jar Packaging with a shelf life of three weeks got an Organoleptic Value of Taste = 5.6 (Kinda Like it), Color Value = 6.0 (Like), Aroma Value = 5.8 (Kinda Like it ) and Value Overal Acceptance = 5.8 (Kinda Like it).